Pengaruh Kualitas Audit dan Perusahaan Suspect terhadap Real Earnings Management - Ferda Puspitaningrum (Jurnal Akuntansi dan Bisnis, 2013)
This study examines the influence of audit quality and suspect firms to real earnings management. In this research, real earnings management measured by three variables of real activities manipulation, real activities manipulation through cash flow from operation (CFO), real activities manipulation through production cost and real activities manipulation through discretionary expense. Real earnings management model based on Roychowdhury (2006) and Inaam et al., (2012). This research was conducted by using secondary data from financial reports. First by performs regression analysis to find the estimated value of abnormal cash flow from operation, production costs and discretionary costs. Next, the three abnormal values will be summed and the regression analysis will be done by using suspect firms and audit quality as independent variables. This aims to test each hypothesis stated. Results of this study shows that audit quality and suspect firms have positive and significant effect on real earnings management.